4R Management of Phosphorus Fertilizer in the Northern Great Plains. Issue 5 (30th May 2019) - Grant, Cynthia A.; Flaten, Don N.
Abstract : Phosphorus (P) fertilizer has played a vital role in increasing the productivity of crop production in the northern Great Plains for approximately 100 years. Throughout this period, agricultural production practices have changed dramatically, while our knowledge of P behavior and beneficial management practices has improved. Some of the more recent and substantial changes in farming practices on the northern Great Plains include widespread adoption of reduced tillage systems, introduction of new crops and high‐yielding cultivars, intensification and extension of crop rotations, development of new fertilizer products, increased appreciation of the role of microbial interactions in P dynamics, and growing concern for the effects of P on water quality. As cropping systems, technology, and societal demands evolve over time, nutrient management practices must also evolve to address concerns and take advantage of emerging opportunities. Classic principles and new P fertilizer technologies and management practices must be integrated into packages of 4R practices that optimize crop yield and agronomic efficiency while minimizing negative environmental impact and conserving P resources. Although a wide range of products and practices can be combined for this approach, placing ammonium phosphate fertilizer in a band, in or near the seed‐row, at the time of seeding and at a rate that matches P removal by the crop generally provides the greatest P efficiency, long‐term sustainability, and environmental protection for small grain, oilseed, and pulse crop production in the northern Great Plains. Core Ideas: 4R stewardship for P fertilization is vital for sustainable crop production. The most efficient sources of P fertilizer for this region are ammonium phosphates. Long‐term sustainable crop production requires P fertilizer rates that match crop removal. Banding P fertilizer in or near the seed‐row is agronomically and environmentally beneficial.